Stochastic production frontier for the Lithuanian family farms - Tomas Baležentis (Journal of Business Economics and Management, 2016)
The research follows neo-classical methodology to analyse the trends of the agricultural efficiency. The paper fits the stochastic production frontier to the micro data describing the performance of the Lithuanian family farms during 2004–2009 in order to define the current trends of efficiency and productivity in the sector. Indeed, this is the first application of stochastic frontiers to gauge the performance of Lithuanian family farms. The technical efficiency of the Lithuanian family farms fluctuated around 80%. The analysis confirmed that the livestock farms were peculiar with higher mean technical efficiency if compared to that of mixed or crop farms. The estimated partial output elasticities imply that the intermediate consumption was the most productive factor, whereas assets were four to six times less productive depending on the farming type. The land factor was peculiar with the lowest partial output elasticities. The research contributes to the wider discussion on the patterns of efficiency and productivity in a transition European Union Member States following the accession.